AgI–KI aerosol catalysts with excellent combustion and nucleation performance for weather modification. Issue 7 (30th September 2021) - Song, Tinglu; Xu, Fan; Li, Xiaodong; Guo, Xiaoyan; Zou, Meishuai; Yang, Rongjie
Abstract : By employing AgI-based aerosols, the nucleation efficiency of ice was enhanced, resulting in a greatly decreased icing mass formed on transmission lines. Abstract : The glaze icing of overhead transmission lines seriously influences the security operation of the power grid, resulting in huge economic loss. Here, by employing AgI–KI aerosol catalysts with good combustion performance, we found that the formation of glaze icing could be controlled and eliminated before it causes damage to transmission lines, as revealed by a 0.5 m 3 low temperature cabinet, a 1 m 3 isothermal cloud chamber and a 60 m 3 environment climate chamber, respectively. The higher nucleation rate (∼10 15 ) of AgI–KI aerosols than the blank (∼10 7 ) was found to be beneficial for deicing performance. Our results suggest that such aerosols could be a better choice for deicing technology.